2000
DOI: 10.1007/s150100070024
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Bactericidal Activity against Group C Neisseria meningitidis in Seronegative Subjects

Abstract: The addition of functional tests to the classical serological determination increases the evidence of previous contact with N. meningitidis antigens by 12%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A previous publication described opsonophagocytic activity in seronegative subjects [10] in the screening phase of the clinical trial reported here. The current study describes opsonophagocytosis and complement-mediated bactericidal killing determined in ex vivo killing curves over a 3-year period following vaccination with the polysaccharide vaccine of group C Neisseria meningitidis.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…A previous publication described opsonophagocytic activity in seronegative subjects [10] in the screening phase of the clinical trial reported here. The current study describes opsonophagocytosis and complement-mediated bactericidal killing determined in ex vivo killing curves over a 3-year period following vaccination with the polysaccharide vaccine of group C Neisseria meningitidis.…”
Section: Introductionmentioning
confidence: 68%
“…In the screening phase of this trial, 12% of the screened subjects who were seronegative (bactericidal antibody titres < 1 : 8 and ELISA antibody titers < 2 µg/ml) demonstrated high bacterial killing activity [10], probably activated by antibodies at levels below the detection limit. In contrast, in this study, 16.6% (2/12) of seroprotected subjects did not have the capacity to kill bacteria in the ex vivo killing curves over the 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…meningitidis is efficiently phagocytosed by polymorphonuclear (PMN) cells (5,8,10), and antibodies specific for group A and C polysaccharides are bactericidal in the presence of peripheral blood polymorphonuclear leukocytes and complement (19). Monocytes can also phagocytose Neisseria species (12,13,16,23).…”
mentioning
confidence: 99%